Dynamic Posture-Related Preoperative Pain as a Single Clinical Criterion in Patient Selection for Extreme Lateral Interbody Fusion Without Direct Decompression. Issue 6 (September 2019) - Lim, Kai-Zheong; Daly, Christopher; Brown, Jessica; Goldschlager, Tony
Study Design: Prospective cohort study. Objectives: Evidence on predicting the success of indirect decompression via extreme lateral interbody fusion (XLIF) is scarce. The authors investigated if patients who could achieve a pain-free position preoperatively would derive clinical benefit from XLIF without direct decompression. Methods: Data from 50 consecutive patients who underwent XLIF with and without direct decompression by a single surgeon from January 2014 to August 2017 was collected. Primary outcome is the rate of failure of patients who underwent XLIF without direct decompression, characterized by persistence of pain postoperatively that required reoperations within 6 months postoperatively. Secondary outcomes are clinical outcomes and patient-reported quality of life outcome data, including visual analogue scale for leg (VASL) and back (VASB) pain, Oswetry Disability Index (ODI), and Physical Component Score (PCS) and Mental Component Score (MCS) of SF-12, for up to 2 years postoperatively. Results: One patient with preoperative dynamic posture-related pain who underwent XLIF without direct decompression subsequently had a reoperation due to persisting pain. Statistically significant improvement was achieved across all patient reported outcomes ( P < .05): improvement of 68% for VASL, 61% for VASB, 50% for ODI, 33% for PCS, and 11% for MCS of SF-12 at last follow-up. Six patients had thigh symptoms that resolved. Conclusion: The simple clinical criterion based on postural pain status preoperatively may help clinicians in patient selection for indirect decompression of XLIF without the need for direct decompression. Further studies with larger cohorts are warranted to establish the validity of the algorithm.